Panoramic imaging : sensor-line cameras and laser range-finders - Huang, Fay (John Wiley & Sons, 2008)
Panoramic imaging is a progressive application and research area. This technology has applications in digital photography, robotics, film productions for panoramic screens, architecture, environmental studies, remote sensing and GIS technology. Applications demand different levels of accuracy for 3D documentation or visualizations. This book describes two modern technologies for capturing high-accuracy panoramic images and range data, namely the use of sensor-line cameras and laser range-finders. It provides mathematically accurate descriptions of the geometry of these sensing technologies and.